UJI EFIKASI EKSTRAK DAUN MAHONI (Swietenia mahagoni (L.) Jaqc.) TERHADAP HAMA ULAT GRAYAK (Spodoptera litura F.) DAN HASIL TANAMAN KACANG TANAH (Arachis hypogaea L.) - Endang Suprapti; Dwi Susilo Utami; Tyas Soemarah K.D; Haryuni (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2020)
Indonesia has a huge, biological resources as a plant which can be used as a pesticide natural mahogany. The plant pesticide vegetable is pesticide, plant are based with the active ingredient and control of organism. Obstacles in cultivation of plant peanuts is Spodoptera litura F. pest attacks. Which result in a decrease in productivity and seeds being broken. The purpose of this evaluation to understand the influence of extract mahogany leaves and intensity of attacks against the percentage caterpillar in plants peanut , to know intervals of time the application of appropriate to reduce the percentage of and intensity of pest attacks , and to know the influence of the interaction of concentration and intervals of time application extract mahogany leaves. This research in a random complete the group consisting of two factors.The first concentration extract leaves mahogany and the second factor intervals of time application .But the research referred to as follows 1 ) the first , the extract leaves mahogany (A) : A0: 0 % (control), A1 : 8% , A2 : 10%, A3: 12% , 2) factors second , the time interval application (B): B1: every day once upon 3 , B2 : every day once upon 5, B3 : every day once upon 7. Every treatment repeated 3 times. The results of the study show concentration extract leaves mahogany to reduce caterpillar grayak pest attacks .Extract leaves mahogany with intervals of time the application had an influence on the percentage and intensity of pest attacks caterpillar and influential on the parameter the results of .The percentage of highest attack A0B3 38,05 % the lowest percentage A3B1 3,91 % as much as . For the intensity of the attack highest A0B3 25,77 % and the lowest A3B1 13,76 % as much as .The results of fresh pods peanut the highest A3B1 (6,0608 t /ha) and the lowest A1B3 with the results of (0,5431 t /ha).